Fabrication of AEI-type aluminosilicate catalyst with sheet-like morphology for direct conversion of propene to butenes. Issue 17 (25th July 2021) - Osuga, Ryota; Takeuchi, Takashi; Sawada, Masato; Kunitake, Yusuke; Matsumoto, Takeshi; Yasuda, Shuhei; Onozuka, Hiroaki; Tsutsuminai, Susumu; Kondo, Junko N.; Gies, Hermann; Yokoi, Toshiyuki
Abstract : A new class of AEI -type aluminosilicates with sheet-like morphology was synthesized by the CGI-assisted method, which showed a higher iso-butene yield than the cubic particle during the PTB reaction. Abstract : AEI -type aluminosilicate zeolites with sheet-like morphology were successfully synthesized by the crystal growth inhibitor (CGI)-assisted method, where cetyltrimethylammonium bromide (CTAB) worked as a CGI. The obtained sheet-like AEI -type aluminosilicates showed a higher yield of butenes and longer catalytic lifetime in the direct conversion of propene to butenes than the conventional sample. The improvement of catalytic performance originated from tuning the molecular diffusion in the zeolite particles. The sheet-like morphology gave a higher molecular diffusivity, and consecutive reactions were suppressed. Moreover, there was a significant difference in the product distribution of butene isomers; linear butenes and iso-butene were the dominant product over the typical AEI -type aluminosilicate with cubic particles induced by the shape selectivity into zeolitic micropores, while the sheet-like one yielded a higher selectivity for iso-butene. It was revealed that the distribution of Brønsted acid sites between internal and external surfaces could be controlled by increasing the external surface area coming from the sheet-like particles.